Nothing - Teller, Janne, 1964-; Aitken, Martin (New York : Atheneum Books for Young Readers, 2010)
When thirteen-year-old Pierre Anthon leaves school to sit in a plum tree and train for becoming part of nothing, his seventh grade classmates set out on a desperate quest for the meaning of life.
1000
Danish Cultural Ministry Prize for best children's/youth book of 2001.
Le Prix Libbylit 2008.
Keywords: Meaning (Philosophy) -- Fiction; Interpersonal relations -- Fiction; Schools -- Fiction